1993
DOI: 10.2337/diacare.16.11.1438
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Impairments in IDDM Patients During Euglycemia and Hypoglycemia

Abstract: In IDDM patients, chronic, structural CNS changes already appear at the brainstem level during euglycemia. Functional, reversible CNS changes, however, seem to emerge during acute deviation from glucose homeostasis in more rostral brain regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Two studies, using AEP techniques, have suggested that conduction through brain-stem structures involved in the auditory pathway was impaired during acute hypoglycaemia in non-diabetic and diabetic subjects [5,6]. In two other studies, however, brain-stem AEPs were not altered by acute hypoglycaemia in adult subjects who had Type I diabetes with strict glycaemic control [7,8] and in non-diabetic volunteers [7].…”
mentioning
confidence: 99%
“…Two studies, using AEP techniques, have suggested that conduction through brain-stem structures involved in the auditory pathway was impaired during acute hypoglycaemia in non-diabetic and diabetic subjects [5,6]. In two other studies, however, brain-stem AEPs were not altered by acute hypoglycaemia in adult subjects who had Type I diabetes with strict glycaemic control [7,8] and in non-diabetic volunteers [7].…”
mentioning
confidence: 99%
“…Neurophysiological changes have been previously described for the condition of induced hypoglycemia in both normal subjects and insulin-dependent diabetic patients (13,14,24,25). In this study, evoked potential recordings, which provide useful information regarding nervous system function, have shown a wide spectrum of abnormalities during the course of spontaneous chronic hypoglycemia in humans.…”
Section: Discussionmentioning
confidence: 86%
“…3,4 In the recent Diabetes Control and Complication Trial (DCCT), severe hypoglycemia occurred three times more often in patients receiving a more intensive insulin regimen, sometimes without having any symptoms.…”
mentioning
confidence: 99%
“…1,2 In recent years, lack of awareness of the symptoms of hypoglycemia has been increasingly recognized as an important factor behind the occurrence of severe hypoglycemia. 3,4 In the recent Diabetes Control and Complication Trial (DCCT), severe hypoglycemia occurred three times more often in patients receiving a more intensive insulin regimen, sometimes without having any symptoms. 5 Currently, there are about 5000 diabetic patients (of all types) followed up in the Security Forces Hospital (SFH), Riyadh, as this hospital is the major referral center for Ministry of Interior employees and their relatives.…”
mentioning
confidence: 99%